2021
DOI: 10.1021/acsmacrolett.1c00470
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Short Semiflexible DNA Polymer Chains in Strong and Moderate Confinement

Abstract: In many technological applications, DNA is confined within nanoenvironments that are smaller than the size of the unconfined polymer in solution. However, the dependence of the diffusion coefficient on molecular weight and characteristic confinement dimension remains poorly understood in this regime. Here, convex lens-induced confinement (CLiC) was leveraged to examine how the diffusion of short DNA fragments varied as a function of slit height by using single-molecule fluorescence tracking microscopy. The dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Although there have been recent advances, little is still understood about the trajectory profiles and confinement nature of DNA travelling through these nanopores [ 160 ]. The influence of the molecular weight and the confinement dimensions on the diffusion coefficient under the confinement regime has been examined by Gregory T. Morrin et al [ 165 ]. They used single-molecule fluorescence-tracking microscopy to take advantage of convex lens-induced confinement (CLiC) to investigate how the diffusion of small DNA fragments varied as a function of slit height.…”
Section: Dna In Confined Geometrymentioning
confidence: 99%
“…Although there have been recent advances, little is still understood about the trajectory profiles and confinement nature of DNA travelling through these nanopores [ 160 ]. The influence of the molecular weight and the confinement dimensions on the diffusion coefficient under the confinement regime has been examined by Gregory T. Morrin et al [ 165 ]. They used single-molecule fluorescence-tracking microscopy to take advantage of convex lens-induced confinement (CLiC) to investigate how the diffusion of small DNA fragments varied as a function of slit height.…”
Section: Dna In Confined Geometrymentioning
confidence: 99%
“…Subsequently, the static and dynamic behaviors of confined polymer chains bacame the subject of extensive theoretical, simulational, and experimental studies. Harden and Doi calculated the diffusion of a single polymer chain in narrow channels by using a combination of the Kirkwood approximation and self-consistent field theory. They found that D ∼ H 0.61 , which is slightly weaker than the scaling of the blob theory.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the weak dependence on slit height suggests that shorter DNA molecules may adopt increasing rod-like conformations and experience weaker excluded-volume interactions as the confinement dimension is reduced. 17 In polyelectrolyte surface diffusion, they found that the diffusion of poly- l -lysine can be affected by the glass surface chemistries. 23 In general, the diffusion of polymer chains will be slower in nano-channels as confinement spaces can inhibit motion.…”
Section: Introductionmentioning
confidence: 99%
“…15 Confinements may greatly affect conformations 16 and dynamics of confined polymer chains. [17][18][19][20][21][22][23] Roopnarine et al determined the diffusion coefficient of dextran and sodium polyacrylate in convex lens-induced confinement using different dynamic microscopy, and they found that polymer diffusion becomes slower in a higher confinement as well as the dextran diffusion remains unchanged near surfactantstabilized hydrophobic surfaces. 18 Davidson et al investigated the diffusion of water-soluble polymers into membranes and found that diffusion becomes slow as the confinement increases.…”
Section: Introductionmentioning
confidence: 99%